Predictors of return on assets and return on equity for banking and insurance companies on Vietnam stock exchange - Lucille V. Pointer; Phan Dinh Khoi (Entrepreneurial Business and Economics Review (EBER), 2019)
Objective: The objective of the article is to empirically examine the predictors of ROA and ROE for banks and insurance firms listed on the Vietnamese stock market. Research Design & Methods: The authors applied a quantitative approach. A basic OLS regression model is used to investigate key proposed predicators of ROA and ROE. Findings: Internal variables are statistically significant predictors for both ROA and ROE in the study, including firm size, book value, return on equity, years in business, and earnings per share. The direction of causality is not consistent across the ratios. Capital structure was significant and negative for ROE. Banks earned lower return on their assets and higher return on their equity than insurance companies. Implications & Recommendations: Given the significance of internal variables such as firm size, return on equity, book value, years in business and earnings per share as predictors of ROA and ROE, management must focus on improving its internal organizational structure which affects these variables. Years in business is significant for both ROA and ROE which may reflect managers' tacit knowledge. Firms should cultivate stability within its managerial staff. To aid future growth, management must secure the proper combination of debt to equity funding. Contribution & Value Added: This article confirms past findings of internal predictors of ROA and ROE in banking. It is one of the first studies to examine predictors of ROA and ROE for firms in the insurance industry.
Keywords: G21; G22; 330; return on assets; return on equity; banking; insurance; GLM; Vietnam